PERANAN AUDIT INTERNAL DALAM DETEKSI DAN MENCEGAH FRAUD (STUDI KASUS PADA UNIVERSITAS NEGERI YOGYAKARTA) - , FAUZAN FIANDREA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The College is an educational entity that manages the funds were sourced from theindividual, the society and the Government therefore colleges have the obligation toperiodically submit a report on the financial management of these funds to its stakeholders. The demands of stakeholders and accountability transparency .... push the management toproduce quality reports that are independent of the elements of fraud. Tighter oversight needsto be done in order to prevent the occurrence of behavior deviations through the improvementof internal control (internal control). The internal audit function should help the company in maintaining effective internal controlsby evaluating the adequacy, efficiency and effectiveness of the controls, as well as encourage increased controls on an ongoing basis. State University of Yogyakarta is one of the leading Universities in Indonesia. Therefore,State University of Yogyakarta must have good internal controls, due to design internalcontrol is good overall, a good internal controls must be designed from small entities. Actionfraud can happen anywhere, but it could have been prevented by the existence of a goodinternal controls within the body of the organization. Realize the importance of the internal audit function within the body corporate, the Organization carried out research regarding internal audit, in particular in the framework ofthe prevention and detection of fraud under the title: x âPERANAN AUDIT INTERNAL DALAM MENDETEKSI DAN MENCEGAH FRAUD (STUDI KASUS PADA UNIVERSITAS NEGERI YOGYAKARTA)â